Integrating Concepts of Counterpublics into Generalised Public Sphere Frameworks: Contemporary Transformations in Radical Forms - Kaiser, Jonas; Rauchfleisch, Adrian (Javnost-The Public, 2019)
Public sphere theory has come to an epistemic crossroads. The rise of right-wing movements in Europe and the U.S., for example, pose a challenge to public sphere theorists. This holds especially true since they make use of social media to articulate their messages, network, recruit, dissent or attack. In this conceptual paper we suggest a functionalist approach that integrates the concept of counterpublics within the public sphere based on the two generalised functions agenda-setting and identity formation. We describe how counterpublics may become regular publics, but also emphasise on how strong collective identities may lead to a vicious cycle of extremism. Based on the examples of the far-right Stormfront forum and the Generation Identity, the concept of the vicious cycle of extremism is being proposed to highlight the internet’s role in the formation and radicalisation of counterpublics.